Twinning rates and social class in Great Britain. Issue 2 (February 1989) - Murphy, M; Botting, B
Abstract : We examined like and unlike sex twinning rates in Great Britain by social class over the period 1974-85. Although twinning rates are believed to have changed over that period, we found no evidence of differential change by social class, suggesting that any factors affecting twinning are widespread in the population.